Allele frequency of muscular genetic disorders in bull-catching (vaquejada) quarter horses - Sperandio, L. M.S. [UNESP]; Lago, G. R. [UNESP]; Albertino, L. G. [UNESP]; Araújo, C. E.T.; Ferreira, C.; Borges, A. S. [UNESP]; Oliveira-Filho, J. P. [UNESP] (Elsevier, 2024)
Quarter horses (QH), a prominent athletic breed in Brazil, are affected by muscular genetic disorders such as myosin-heavy chain myopathy (MYHM), polysaccharide storage myopathy (PSSM1), hyperkalemic periodic paralysis (HyPP), and malignant hyperthermia (MH). Bull-catching (vaquejada), primarily involving QH, is a significant equestrian sport in Brazil. Since the allele frequencies (AF) of MYHM, PSSM1, HyPP, and MH in vaquejada QH remain unknown, this study evaluated the AF in 129 QH vaquejada athletes, specifically from the Brazilian Northeast. These variants were exclusively observed in heterozygosity. The MYHM exhibited the highest AF (0.04 ±0.01), followed by PSSM1 (0.01 ±0.01) and the HyPP variant (0.004 ±0.01), while the MH variant was not identified in this study. This study represents the first identification of these variants in vaquejada QH, emphasizing the need to implement measures to prevent the transmission of pathogenic alleles and reduce the occurrence of clinical cases of these genetic diseases.
Keywords: HyPP; MH; MYHM; Myopathy; PSSM1